2019
DOI: 10.3389/fphar.2019.00024
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Function of Lemur Tyrosine Kinase 2 Network

Abstract: Lemur Tyrosine Kinase 2 (LMTK2) is a recently cloned transmembrane protein, actually a serine/threonine kinase named after the Madagascar primate lemur due to the long intracellular C-terminal tail. LMTK2 is relatively little known, compared to other kinases but its role has been increasingly recognized. Published data show that LMTK2 regulates key cellular events, including endocytic trafficking, nerve growth factor signaling, apoptosis, and Cl− transport. Abnormalities in the expression and function of LMTK2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 76 publications
(156 reference statements)
0
13
0
Order By: Relevance
“…A variant within LMTK2 , rs11762534, which is also an eQTL for many genes, displays evidence of selection (s=0.005; logLR = 16.49) and is associated with blood cell percentages and malignant neoplasm of prostate. LMTK2 encodes a serine/threonine kinase that is implicated in diverse cellular processes including apoptosis, growth factor signalling and appears essential for spermatogenesis in mice (Kawa et al, 2006; Cruz et al, 2019). Outside the Middle East, the variant is highly stratified and is present at the highest frequency in Europeans (1KG, 45%), but we find it at 66% frequency in the Arabian populations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A variant within LMTK2 , rs11762534, which is also an eQTL for many genes, displays evidence of selection (s=0.005; logLR = 16.49) and is associated with blood cell percentages and malignant neoplasm of prostate. LMTK2 encodes a serine/threonine kinase that is implicated in diverse cellular processes including apoptosis, growth factor signalling and appears essential for spermatogenesis in mice (Kawa et al, 2006; Cruz et al, 2019). Outside the Middle East, the variant is highly stratified and is present at the highest frequency in Europeans (1KG, 45%), but we find it at 66% frequency in the Arabian populations.…”
Section: Resultsmentioning
confidence: 99%
“…We also identified additional variants that show an increase in frequency recently ( Figure 4C-D. A variant within LMTK2, rs11762534, which is also an eQTL for many genes, displays evidence of selection (s=0.005; logLR = 16.49) and is associated with blood cell percentages and malignant neoplasm of prostate. LMTK2 encodes a serine/threonine kinase that is implicated in diverse cellular processes including apoptosis, growth factor signalling and appears essential for spermatogenesis in mice (Kawa et al, 2006;Cruz et al, 2019).…”
Section: Selectionmentioning
confidence: 99%
“…This dual role of PP1γ2 is intriguing because loss of the enzymes of cAMP metabolism and action, sAC or PKA in testis, does not impair sperm morphogenesis or sperm formation. It is likely that other serine/threonine protein kinases along with PP1γ2 are responsible for regulation of protein phosphorylation during spermatogenesis (Kawa et al, 2006;Xu et al, 2007;MacLeod et al, 2014;Cruz et al, 2019). Due to its requirement in spermatogenesis, it is not possible to obtain sperm lacking PP1γ2, which is a limitation for the study of the enzyme in mature sperm.…”
Section: Protein Phosphatase Isoform Pp1γ2 In Sperm Functionmentioning
confidence: 99%
“…Lemur tyrosine kinase 2 (LMTK2), also known as cyclin-dependent kinase-5 (CDK5)/p35 regulated kinase (cprk), kinase/phosphatase/inhibitor-2 (KPI2), brain-enriched kinase (BREK), and apoptosis-associated tyrosine kinase (AATYK)-2, is a member of the lemur family of membraneanchored kinases. Despite its naming, LMTK2 is actually a Ser/Thr kinase that has been identified to interact with a restrict number of proteins, although related to different signaling pathways and key cellular processes [reviewed in (1)]. Earlier studies have shown that LMTK2 interacts with CDK5 and protein phosphatase 1 (PP1c) (2)(3)(4)(5), cystic fibrosis transmembrane conductance regulator (CFTR) (6), myosin VI (7,8), and anti-and pro-apoptotic proteins, such as B-cell lymphoma (BCL)2, BCL-xL and BCL2-interacting mediator of cell death (BIM) (9).…”
Section: Introductionmentioning
confidence: 99%